Composição florística e estratégias de dispersão de espécies lenhosas em uma floresta ribeirinha, arroio Passo das Tropas, Santa Maria, RS, Brasil - Budke, Jean Carlos; Athayde, Eduardo Anversa; Giehl, Eduardo Luís Hettwer; Záchia, Renato Aquino; Eisinger, Sonia Maria (My University, 2005)
Riverside forests are extremely important because they play a great role as biological corridors, keeping the water quality and of the ictiological fauna. In the context of its dynamical process, the dispersal of plant diaspores is little known. The aims of this study are to describe the floristic composition and the seed dispersal strategies of woody species in a riveside forest fragment in the municipality of Santa Maria, southern Brazil. All the individuals with pbh > 15 cm were sampled into 100 quadrats of 100 m2. The dispersion mechanisms were described through field observations and by the use of specialized references. Sixty-eight species from 31 botanical families were found. Myrtaceae (18), Fabaceae (7), Asteraceae, Sapindaceae, Euphorbiaceae, and Flacourtiaceae, with three species were the families with highest species richness. Seventy-two percent of the species were animal-dispersed, 24% wind-dispersed and 4% selfdispersed. Considering the dispersal modes and the abundance of the individuals, the dispersal mode includes 45% animal-dispersed individuals; 43% wind-dispersed, and 12% self-dispersed. The preponderance of animal-dispersed species points out the importance of the biotic agents on the maintenance of the gene flow in forest communities. Copyright © 2008 Fundação Zoobotânica do RS.
Floristic composition and seed dispersal strategy of woody species in a riverside forest, Passo das Tropas Stream, Santa Maria, RS, Brazil
Keywords: Frugivory; Plant diaspores; Southern Brazil